HKS Misinfo Review 2020
DOI: 10.37016/mr-2020-014
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns to prevent the spread of misinformation during epidemics.

Abstract: Identifying patterns to prevent the spread of misinformation during epidemicsThis paper discusses patterns of public health misinformation observed during infectious disease epidemics. Specifically, we group epidemic-related misinformation into four categories: transmission, prevention, treatment, and vaccination. By developing tools, algorithms, and other resources around these categories, institutions, companies, and individuals can proactively limit and counter the spread of misinformation and its potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Twitter users often fail to detect rumors (Wang & Zhuang, 2018). Misinformation for infectious diseases has focused primarily on issues related to transmission, prevention, treatment, and vaccination (Nsoesie & Oladeji, 2020). The false claims in misinformation can produce negative health outcomes and lead people to take harmful actions in search of a remedy, such as gargling bleach in attempt to eliminate a virus.…”
Section: Discussionmentioning
confidence: 99%
“…Twitter users often fail to detect rumors (Wang & Zhuang, 2018). Misinformation for infectious diseases has focused primarily on issues related to transmission, prevention, treatment, and vaccination (Nsoesie & Oladeji, 2020). The false claims in misinformation can produce negative health outcomes and lead people to take harmful actions in search of a remedy, such as gargling bleach in attempt to eliminate a virus.…”
Section: Discussionmentioning
confidence: 99%
“…By harnessing a term/hashtag that was already in use on social media, the film's promoters had access to pre-existing and captive social networks through which to initiate the spread of the documentary. Online resources are emerging to investigate and track different conspiracy theories and viral misinformation related to COVID-19 (Chen et al, 2020;National Press Foundation, 2020;Nsoesie & Oladeji, 2020). Such tools support journalists as they respond in real-time to developing stories about viral misinformation, and public health researchers must adapt to evolving technologies.…”
Section: Plandemic As a Case Study For Social Media Misinformationmentioning
confidence: 99%
“…Another salient example is the COVID-19 pandemic. For instance, Nsoesie and Oladeji [ 17 ] investigated the impact of misinformation on public health during the COVID-19 pandemic. They found that COVID-19 misinformation prevented people from demonstrating effective health behaviors and weakened the public’s trust in the health care system.…”
Section: Introductionmentioning
confidence: 99%